2018
DOI: 10.1002/acm2.12480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation of Dosimetry Check™ for TomoTherapy® delivery quality assurance

Abstract: PurposeThe delivery quality assurance (DQA) of intensity‐modulated radiotherapy (IMRT) plans is a prerequisite for ensuring patient treatments. This work investigated the clinical usefulness of a new DQA system, Dosimetry Check™(DC), on TomoTherapy®‐based helical IMRT plans.MethodsThe DQA was performed for 15 different TomoTherapy®‐based clinical treatment plans. In Tomotherapy® machines, the couch position was set to a height of 400 mm and the treatment plans were delivered using QA‐Treatment mode. For each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(23 reference statements)
2
7
0
1
Order By: Relevance
“…This in-treatment assessment confirms the variation from the first reference sinogram. Additionally, a system is also being developed to calculate and evaluate the dose distribution in the body using in vivo calculated images that have been generated [24]. In this software, the sinogram is deconvoluted by a kernel specifically adapted to the MVCT detector to obtain the corresponding primary treatment fluence map.…”
Section: Influence Of Results By Each Treatment Sitementioning
confidence: 99%
“…This in-treatment assessment confirms the variation from the first reference sinogram. Additionally, a system is also being developed to calculate and evaluate the dose distribution in the body using in vivo calculated images that have been generated [24]. In this software, the sinogram is deconvoluted by a kernel specifically adapted to the MVCT detector to obtain the corresponding primary treatment fluence map.…”
Section: Influence Of Results By Each Treatment Sitementioning
confidence: 99%
“…The feasibility of using MVCT measured LOTS to reconstruct 3D dose distribution on to patient CT datasets have been reported by several authors either by using in-build or independent dose reconstruction algorithm in routine clinical cases [13][14][15][16][17][18][19]21]. The excellent agreement both in absolute dose (< ± 1.8%), 2Dγ (> 97%), 3Dγ (> 96%) and 2Dγ vs 3Dγ variation (≤ 2.5%) between reconstructed dose from LOTS as compared to planned, ion chamber and ArcCHECK measurement, in all ten non-TMI patients validated the accuracy and reliability of LOTS reconstructed method in Delivery Analysis against the standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…The unique design of megavoltage cone beam computed tomography (MVCT) detectors in HT allows measurement of delivered sinogram (dose fluence) prior to or during treatment. Several studies have reported the feasibility of using measured sinogram to reconstruct 3D dose distribution on to the patient CT datasets using in-build or independent dose reconstruction algorithm in routine clinical cases [13][14][15][16][17][18][19]. To the best of our knowledge, no study has been conducted to provide an accurate and yet efficient PSQA of TBI/TMI/ TMLI patients treated on HT.…”
Section: Introductionmentioning
confidence: 99%
“…The unique design of megavoltage cone beam computed tomography (MVCT) detectors in HT allows measurement of delivered sinogram (dose uence) prior to or during treatment. Several studies have reported the feasibility of using measured sinogram to reconstruct 3D dose distribution on to the patient CT datasets using in-build or independent dose reconstruction algorithm in routine clinical cases [13][14][15][16][17][18][19]. To the best of our knowledge, no study has been conducted to provide an accurate and yet e cient PSQA of TBI/TMI/TMLI patients treated on HT.…”
Section: Introductionmentioning
confidence: 99%